Geografia e Literatura: A representação de Goiânia em fragmentos de viver é devagar de Brasigóis Felício - SOUSA, Andréia Aparecida Moreira de (2008)
The starting goal of this study case is to go through a path that has been built between the geography and the literature by the piece of work analyses: Viver é devagar . For a theoretical basis, this work dealt with the geographic categories of place, landscape, urban space, and time to the social representation theory. In the literary work Viver é devagar , the author, as a spectator and actor, takes over the urban space in Goiânia . Place is his starting point, and landscape is his narration object. The narration begins in his lived place in a metropolis. The conceptual structure of this work starts from a symbolic dimension, because it refers to cognitive contents that allow a person to be someone who knows and interprets the reality. The author demonstrates the representations of affective life, values, believes, knowledge, dreams, hopes, and expresses a way to communicate to the world that surrounds him through literature. The methodology that best fits this research is the qualitative one. Thus, in this work, the researcher became a spokeswoman to the Felicios chronics. She constant tried to reveal what is implicit in the author s city. A question arises: Does the literary work that has been studied offer enough categories and concepts to represent the social historic process in Goiânia ? To answer to this question, several geographers and authors from different areas were studied to establish a dialog through readings, reflections, and analyses concerning to geography and literature.